Survey of users’ level of satisfaction toward inclusive management and marketing of library service in Nigeria - Obinyan, Oluwatoyin (Folia Toruniensia, 2021)
Aim: Information and Communication Technologies (ICTs) brought significant innovation and improvement to library services and methods of meeting user needs. Assessment of user satisfaction with the various library services is an important variable toward inclusive library management and marketing of library services in the 21st century. With the application of ICTs bringing about different resources and various accessibility modes (print and online), it became necessary to investigate user satisfaction with various available library resources and services. Methods: The study addressed user satisfaction using adapted customer satisfaction scores (CSAT) metric with Rodski Survey to elicit information from 560 respondents that visited the library within the space of one week. The questionnaire was given to the respondents during their library visit twice daily for one week and the process excluded those that have filled the questionnaire before. Results: The data collected were analysed using descriptive statistics. The findings revealed the level of user satisfaction to be average. It was also discovered that the resources in the library did not meet their information needs as the majority responded that the resources are inadequate and the overall assessment of their interaction with librarians is excellent despite the inadequate resources. Conclusion: Based on the findings, recommendations were made to create a holistic marketing strategy to improve usability of the library, to acquire more resources and funding to meet user expectations, and to address the need for adequate management of library resources.